Photogrammetric evaluation of corrective surgery for trigonocephaly. Issue 1 (January 2022) - Kuehle, R.; Ewerbeck, N.; Rückschloß, T.; Ristow, O.; El Damaty, A.; Freudlsperger, C.; Hoffmann, J.; Engel, M.
Abstract: The aim of this study was to capture preoperative, postoperative, and follow-up head shapes of male trigonocephaly patients who underwent fronto-orbital remodelling (FOR), using three-dimensional (3D) photography. Fifty-seven male infants with metopic synostosis operated on using standardized FOR during a 5-year period were included. All measurements were compared with those of an age-matched healthy control cohort ( n = 253 for early postoperative comparison, n = 43 for the 1-year follow-up comparison) to determine the effect of FOR at 14 days and at 1 year post-surgery. Intracranial volume, frontal angle, nasofrontal angle, interfrontoparietal–interparietal ratio, and inter-orbital distances were measured 1 day preoperatively, 14 days and 1 year postoperatively. Mean age at surgery was 9.7 ± 1.1 months. Prior to surgery, boys with metopic synostosis showed a reduced intracranial volume (−7.0%, P < 0.001), frontal angle (−10.2%, P < 0.001), interfrontoparietal–interparietal ratio (−4.9%, P < 0.01), and orbital distances (−6.5%, P < 0.001) compared to the reference group, but values did not differ significantly from the specific control group after surgery (all P > 0.05). This was consistent by the time of the follow-up examination. Corrective surgery should therefore aim to achieve volume expansion and correction of the deformity. Furthermore, 3D photogrammetry provides a valuable alternative to computed tomography scans in the diagnosis of metopic synostosis, significantly reducing the amount of radiation exposure to the brain.